Advertising 2007 - Pedersen, B. Martin, 1936-; Carnick, Anna N. (Graphis, 2006)
GraphisAdvertisingAnnual2007 is the global Advertising community's premiere showcase o print ads featuring over 300 companies of single ads and compaigne, plus detailed credits and indexes.This eyquisite annual is arranged into trade categories such as Automotive, Beauty & Cosmetics, Food Corporate and Sports. This year's edition offers a global perspective on the Advertising industry with feature profiles ov Kevin Amter of New York's Ogilvy & Mather, Mariusz Jan Demner of Austria's Demner, Merlicek & Bergmann, Frensesc Petit of DPZ Brazil, and Santaya Lohaphantakit and Pijarinee Kamolyabutr of the Thai firm, Ongoing.
Obshuje rejstřík a adresář.
Keywords: reklama a propagace; reklamní fotografie; plakáty; venkovní reklama; ročenky